Justice in Japan (Supreme Court of Japan, 1978)
This book consists of the following many parts: political structure and judicial system under present constitution, routine work of the supreme court, participation of laymen in judicial proceeding, vicissitudes of law and history of justice from ancient to modern period, Meji constitution and development of modern political structure and Judicail system.